THE IMPORTANCE OF VEGETABLE GROWING IN THE DYNAMIZATION OF THE PRODUCTIVE CHAIN OF VEGETABLES IN FAMILY AGRICULTURE IN BRAZIL (REMUNOM, 2025)
Family farming in Brazil accounts for 77% of rural establishments and plays an essential role in food production for the domestic market, with olericulture standing out as a strategic activity for productive diversification, employment generation, income, and strengthening food security. The production of vegetables, primarily carried out on small properties, faces challenges such as limited access to technology, credit, infrastructure, and marketing channels, factors that hinder its growth and competitive market integration. Nevertheless, olericulture proves to be an efficient and sustainable alternative to invigorate the agricultural production chain, leveraging the growing demand for fresh and healthy foods, while promoting more responsible agricultural practices. The history of vegetable cultivation in Brazil dates back to Portuguese colonization, which introduced various species adapted to local conditions, establishing the activity as an important source of income, especially in the Southeast and South regions, with potential for expansion in other areas like the Northeast. The study indicates that, to strengthen the family farming production chain, it is crucial to implement specific public policies, invest in accessible technologies, and reinforce marketing networks, thereby promoting sustainable rural development, social inclusion, and environmental preservation.